A Review on Application of Noble Metal-Free Materials/ZrO2 Nano-photocatalysts for Removal of Organic Pollutants and Heavy Metals - Marjan Tanzifi (Journal of Water and Environmental Nanotechnology)
Photocatalysis process is widely investigated for removal of various pollutants from water and wastewater. ZrO2 is a common metal oxide semiconductor with excellent optical properties, non-toxicity, stability in acidic and alkaline media, and high thermal stability. The appropriate potential levels of conduction and valence bands of this metal oxide are among its other desirable properties. Therefore, ZrO2 is a promising candidate for the photocatalysis process and the photocatalytic degradation of various pollutants in water treatment. However, the pure ZrO2 is not efficient enough due to its high recombination rate of electron-hole pairs and wide bandgap. The combination of ZrO2 with other semiconductors is an effective strategy to tackle these disadvantages. This not only delays the recombination of electron-hole pairs but also reduces the bandgap of the composite, improving light absorption in the visible region in many cases. In the photocatalysis process, noble metal-free materials have been gaining traction, as they are inexpensive and eco-friendly, and therefore applicable for large-scale industrial uses. This paper reports a review of the combination of noble metal-free materials with ZrO2 and its effects on optical properties, surface, and water treatment efficiency. This study also reviews several complex mechanisms of active species generation and pollution degradation through ZrO2-based photocatalysts. The photocatalytic activities of photocatalysts are then analyzed under different experimental conditions. Finally, a few suggestions are made for future research avenues, the systematic design of ZrO2-based photocatalysts, and the synthesis of photocatalysts activated in visible-light with high efficiency in the removal of pollutants from the water.